Integrated Lean-Route Planning model for incident reduction in a courier company: An Empirical Research in Perú - Gonzalez-Ureta, Jose Carlos (2022)
Currently, according to INEI in Peru, the courier sector has suffered a 26% contraction in demand. This means that SMEs belonging to the commerce and courier sector are facing great competition in the market due to the reduction in demand and that the same supply is maintained, i.e., the market has become more competitive. For this reason, SMEs that do not take into consideration this context present problems within their deliveries, these incidences harm the profitability of the company, which leads to a reduction in the level of service. This problem is mainly caused by an inadequate digitization method, an inadequate route assignment and over-deliveries produced by an inadequate plant distribution. To solve this problem, this research proposes an operations model based on Route Planning, SLP and Work Study tools. The research was able to reduce the delivery time by 18.6%, the percentage of classified documents was increased by 29.15% and the percentage of incidents by less than 3%, thus increasing the service level by 22%.